IMPLEMENTASI MODEL PEMBELAJARAN DRAMA DENGAN STRATEGI TEAMS GAMES TOURNAMENT (TGT) BERBASIS DONGKREK - Dwi Rohman Sholeh; Herman J. Waluyo; Setya Yuwana Sudikan; Nugraheni Eko Wardani (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract: This research is meant to: (1) describe the planning of Drama learning using Dongkrek-based Teams Games Tournament (TGT) strategy, (2) describe the implementation of Drama learning using Dongkrek-Based TGT strategy, and (3) describe the obstacles faced by the lecturers and students in drama learning using Dongkrek-Based TGT strategy. This descriptive qualitative research took place in IKIP PGRI Madiun, East Java. The result shows that (1) The lecturer who responsible for the planning of Drama learning using Dongkrek-Based TGT strategy has implemented the designed syllabus while the objectives has been in accordance with the Standard Competency and Basic Competence. Furthermore, the syllabus has includes the complete implementation procedures starting from initial activity of apperception, elaboration, confirmation and motivation. Main activities includes exploration, elaboration and confirmation followed by closing. (2) The implementation of Drama learning using Dongkrek-based TGT strategy included ‘Practice/performance test” in the syllabus but performed written test in the implementation while giving assignment to the student. In addition, there are some points of indicators which have not been achieved by students and didn’t received any special attention from the lecturer. The learning objectives have been in accordance with the Standard Competency and Basic Competency of the syllabus. (3) Obstacles faced by lecturer and students in the implementation of drama learning using Dongkrek-Based TGT strategy proved to be joyful learning as it comes from local culture called Dongkrek as students gained immediate competency on literacy instead of the theory. Abstrak: Penelitian ini bertujuan untuk: (1) mendeskripsikan perencanaan pembelajaran drama dengan strategi Teams Games Tournament (TGT) berbasis dongkrek, (2) mendeskripsikan penerapan pembelajaran drama dengan strategi TGT berbasis dongkrek, dan (3) mendeskripsikan kendala-kendala apa sajakah yang dihadapi dosen dan mahasiswa dalam pembelajaran drama dengan strategi TGT berbasis dongkrek. Bentuk penelitian ini adalah deskriptif kualitatif yang mengambil lokasi di IKIP PGRI Madiun Jawa Timur. Hasil penelitian ini menunjukkan bahwa (1) Dosen pengampu dalam perencanaan pembelajaran drama dengan strategi TGT berbasis dongkrek, sudah mengikuti silabus yang dibuat, tujuan sudah sesuai dengan SK dan KD yang digunakan. Kemudian silabus langkah-langkah pembelajaran sudah lengkap dimulai dari kegiatan awal yang melingkupi apersepsi, elaborasi, konfirmasi dan motivasi. Kegiatan inti melingkupi eksplorasi, elaborasi, dan konfirmasi, kemudian penutup. (2) Penerapan pembelajaran drama dengan TGT berbasis dongkrek pada teknik penilaian pada silabus dicantumkan “tes praktik/ kinerja” namun dosen lebih kepada tes tulis ketika memberikan tugas mahasiswa, ada pula beberapa poin indikator yang belum mampu dicapai oleh mahasiswa dan tidak mendapat perhatian khusus dari dosen. Tujuan pembelajaran juga sudah sesuai dengan SK dan KD pada silabus. (3) Kendala-kendala dosen dan mahasiswa dalam pembelajaran drama dengan strategi TGT berbasis dongkrek, karena sebuah pembelajaran yang berangkat dari sebuah kesenian lokal yaitu kesenian dongkrek maka pembelajaran drama untuk mahasiswa menyenangkan (joyful learning) karena mahasiswa mendapatkan pengalaman langsung tentang kompetensi kesastraan dan bersastra dan tidak hanya berteori.Permalink/DOI: http://doi.org/10.15408/dialektika.v6i1.9679